2021
DOI: 10.1038/s41420-021-00624-8
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in osteoporosis: expression, functions and roles

Abstract: Osteoporosis, which is caused by an imbalance in osteoblasts and osteoclasts, is a global age-related metabolic disease. Osteoblasts induce osteocyte and bone matrix formation, while osteoclasts play an important role in bone resorption. Maintaining a balance between osteoblast formation and osteoclastic absorption is crucial for bone remodeling. Circular RNAs (circRNAs), which are characterized by closed-loop structures, are a class of novel endogenous transcripts with limited protein-coding abilities. Accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Osteoporosis occurs due to excessive bone resorption and impaired bone formation ( 41 ). Accumulating evidences have suggested that dysregulated circRNAs are associated with the occurrence and progression of osteoporosis ( 42 , 43 ). However, the specific role of the circRNA-related network remains mostly undescribed in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis occurs due to excessive bone resorption and impaired bone formation ( 41 ). Accumulating evidences have suggested that dysregulated circRNAs are associated with the occurrence and progression of osteoporosis ( 42 , 43 ). However, the specific role of the circRNA-related network remains mostly undescribed in osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts contain some lysosomes, which are rich in acid proteolytic enzymes. Under pathological conditions, once the rate of bone resorption by osteoclasts exceeds the compensatory capacity of bone formation, bone loss begins and continues for a long time ( Luo et al, 2021 ; Rauner et al, 2021 ). Hence, inhibiting the hyperactivity of osteoclasts is a noteworthy point for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…In osteogenesis regulation, circRNAs could promote osteogenesis through upregulating FOXO1 in OP [ 137 ]. Further, circRNAs including CDR1, CDK8, and SIPA1L1 are extensively implicated in osteogenesis differentiation [ 144 ].…”
Section: Ncrnas and Bone Diseasesmentioning
confidence: 99%
“…This was upregulated in maxillary sinus membrane stem cells: circRNA_33287 downregulation inhibited several osteogenic biomarkers, such as RUNX2, ALP, and Osterix, while the upregulation exerted the opposite effect. However, circRNA_33287 is capable of inducing osteogenesis [ 144 , 147 ].…”
Section: Ncrnas and Bone Diseasesmentioning
confidence: 99%